The Application of 4Å Molecular Sieves in Organic Chemical Syntheses: An Overview - Magyar, Ágnes; Juhász, Kinga; Hell, Zoltán (Synthesis, 2020)
In the last two decades, considerable attention has been devoted to the use of 4Å molecular sieves (MS 4A) in organic chemical syntheses. Initially, they were applied as drying agents in order to dry gases, solvents and liquid reagents. Nowadays, there is a growing tendency to apply MS 4A as an additive, catalyst, co-catalyst or catalyst support in organic reactions. In this review, we aim to summarize the recent examples of organic syntheses promoted by MS 4A from 1997 to 2020. We hope to provide the reader with an overview of the potential of MS 4A in the field of organic synthesis.1 Introduction2 Application as an Additive3 Application as Catalyst4 Application as Co-catalyst5 Application as Support6 Conclusion
Keywords: molecular sieves; additive; catalyst; co-catalyst; support; organic synthesis; green chemistry